2023
DOI: 10.1101/2023.09.21.23295929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Menstrual Cycle and Menopause on Human Gastric Electrophysiology

Alexandria H Lim,
Chris Varghese,
Gabrielle Sebaratnam
et al.

Abstract: Chronic gastroduodenal symptoms disproportionately affect females of childbearing age; however, the effect of menstrual cycling on gastric electrophysiology is poorly defined. To establish the effect of the menstrual cycle on gastric electrophysiology, healthy subjects underwent non-invasive Body Surface Gastric Mapping (BSGM; 8x8 array), with validated symptom logging App (Gastric Alimetry, New Zealand). Participants were premenopausal females in follicular (n=26) and luteal phases (n=18). Postmenopausal fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The most notable change was in Principal Gastric Frequency, which was elevated with exogenous hormone delivery, particularly in formulations containing significant quantities of progestogen. This finding is consistent with a separate study recently performed by our group, which showed that similar elevations in gastric frequency occur normally during the luteal phase of the menstrual cycle in women not taking hormonal contraception when circulating progesterone is also elevated (38). Taken together, these data likely explain why females exhibit higher overall gastric frequencies than males in normative range datasets (25).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The most notable change was in Principal Gastric Frequency, which was elevated with exogenous hormone delivery, particularly in formulations containing significant quantities of progestogen. This finding is consistent with a separate study recently performed by our group, which showed that similar elevations in gastric frequency occur normally during the luteal phase of the menstrual cycle in women not taking hormonal contraception when circulating progesterone is also elevated (38). Taken together, these data likely explain why females exhibit higher overall gastric frequencies than males in normative range datasets (25).…”
Section: Discussionsupporting
confidence: 93%
“…While our study did not specifically address causality, a causal link can be reasonably postulated between hormonal contraception and nausea due to consistent and coherent evidence across adjacent literature, including temporal and dose-response relationships, as well as biological plausibility (35,36). For example, nausea and vomiting are commonly observed during fluctuations or surges in female sex hormones, as seen in menstrual cycling (18,37,38), pregnancy (39,40), as a side-effect of initiating hormonal contraception in healthy women (41,42); (4346), and following the administration of emergency contraceptives (4346). Symptoms have also been noted to fluctuate across the menstrual cycle in patients with gastroparesis, being heightened in the luteal phase (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research has shown no significant differences in the results of EGG 56 or BSGM 57 for calorie‐matched meals with different compositions. In addition, we did not account for menstrual cycle variability in premenopausal female subjects, with elevations in Principal Gastric Frequency recently shown to occur during the luteal phase 58 . Future research is needed to investigate the effect of the menstrual cycle on the reproducibility of the Gastric Alimetry metrics.…”
Section: Discussionmentioning
confidence: 99%